Effect of climate on maximum oxygen consumption among elite football players / Norasrudin Sulaiman - Sulaiman, Norasrudin; Hushin Amri, Hasnol Faizal; Che Mat, Hisyem; Muhamed Kassim, Rezian-Na (Research Management Institute (RMI), 2013)
The maximum oxygen consumption (VO2max) level has been indicated to influence the technical and tactical performance during the football game. There are many variables that are considered as the factors that influenced the VO2max level of the player. One of the major factors that often been studied is the climate. The purpose of current study was to determine effect of climate on maximum oxygen consumption among elite football players. Fifteen (n=15) elite male football (mean±SD aged, 21.3± 3.4 years old; height, 167.7± 10.6 cm and; weight, 59.4± 3.1 kg) players who represent university in Malaysian Premier Football League are willing to participate in this study. All subjects underwent the bleep test during morning (T: 29.7°C, H: 80%) and evening (T: 32.6°C, H: 63%) to measure their VO2max level in both conditions. Subjects also need to go for blood sampling immediately after the Bleep Test. The result from test tests showed that there are no significant differences of the VO2max level and the lactate production between the two climates conditions. Thus, it can be conclude that the tested climate has no significant effects on VO2max among elite football players.